Sistema produto-serviço e servitização : pesquisa-ação em uma empresa de manufatura engineer to order - Braga Júnior, Antonio Erlindo (2017)
The Product-Service System (PSS) presents to companies a single value offer to the combination of products and services designed to meet the customer demands. The PSS has been a rising alternative for manufacturing companies that seek primarily to improve their competitiveness in an increasingly undifferentiated market. There is a growing interest in the PSS development, as shown in the increasing number of publications, in Brazil and abroad, that produces diverse approaches on the subject. Conversely, several authors on this field report a lack of research on the PSS development, with little information on how the designing process change in supplying a pure product instead of supplying a product combined with a service. Recently, many methods and tools for the construction of PSS have been developed; however, there are no records on how to use these means concretely in the design process. There are successive recommendations on how to build a body of knowledge to eliminate this hiatus in the literature. The purpose of this thesis is to develop guidances on the implementation of PSS in manufacturing companies migrating from a pure product offering to a product-service one by an Action-Research method. In order to do so, a PSS was implemented in a manufacturing company that works on an engineer to order model, and from that starting point, a set of guidances was developed to aid on future implementations, as well as on future researches. As a result, we also found two unforeseen steps in the original PSS development method: the preparatory step and the post-development step, which are pertinent steps for the increase of the process’ effectiveness increase. These results provide a more robust PSS development process and will facilitate the work of future PSS developers.